Relating Democratic and Scientific Ethos in Academic Self-Governance: Governing Science Through Peer Review and the Democratizing Potential of Lotteries - Schendzielorz, Cornelia; Reinhart, Martin (Serendipities. Journal for the Sociology and History of the Social Sciences, 2022)
Robert K. Merton envisions science as embedded in a social order and explicitly links the ethos of science and the ethos of democracy. This contribution argues that the Mertonian norms are best seen as a set of procedural norms. Thus, the normative integration of science and society is to be conceived by means of the procedures that form the "in-between" of academia and democratically governed societies. We elaborate how peer review can be understood as a central mechanism of self-government in science. We analyze to what extent the governance of science through peer review aligns with the Mertonian democratic ethos. We investigate to what extent lotteries as a procedural element may hold the potential for new linkages between science and (democratic) social order. In conclusion, we summarize the benefits of conceiving of Merton’s norms as procedural norms with regard to the ethos as well as the autonomy of science considering the integration of scientific and social order.